2010
DOI: 10.1016/j.ejpain.2009.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term facilitation of nociceptive withdrawal reflexes following low‐frequency conditioning electrical stimulation: A new model for central sensitization in humans

Abstract: Central sensitization is believed to be one of the key mechanisms behind chronic pain conditions, and several models have been developed in order to characterize this phenomenon in humans. One of these models relies on conditioning electrical stimulation to elicit long-lasting effects on the nociceptive system. The aim of this study was to evaluate these effects using an objective electrophysiological measurement, the nociceptive withdrawal reflex (NWR). Long-term changes in spinal nociception after high- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…Previous studies have reported conflicting evidence on how HFS-and capsaicin-induced central sensitization influence RIII reflex size (Andersen et al, 1995;Andersen et al, 1996;Manresa et al, 2010). While some studies have reported that central sensitization alone does not increase RIII reflex size (Andersen et al, 1995;Andersen et al, 1996;), others have shown that central sensitization induced by continuous low-frequency stimulation (Manresa et al, 2010) or concomitant thermal stimulation (Andersen et al, 1995) increases RIII reflex size, thus indicating that the modulation of this variable likely requires ongoing somatosensory afferent summation to the dorsal horn. Accordingly, we did not find any RIII reflex size modulation probably because HFS and topical capsaicin elicited short-term painful sensations and did not trigger ongoing afferent summation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported conflicting evidence on how HFS-and capsaicin-induced central sensitization influence RIII reflex size (Andersen et al, 1995;Andersen et al, 1996;Manresa et al, 2010). While some studies have reported that central sensitization alone does not increase RIII reflex size (Andersen et al, 1995;Andersen et al, 1996;), others have shown that central sensitization induced by continuous low-frequency stimulation (Manresa et al, 2010) or concomitant thermal stimulation (Andersen et al, 1995) increases RIII reflex size, thus indicating that the modulation of this variable likely requires ongoing somatosensory afferent summation to the dorsal horn. Accordingly, we did not find any RIII reflex size modulation probably because HFS and topical capsaicin elicited short-term painful sensations and did not trigger ongoing afferent summation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that the RIII reflex threshold is reduced during capsaicin-induced central sensitization (Grönroos and Pertovaara, 1993;Andersen et al, 1995), as well as in patients with chronic pain (García-Larrea and François, 1990;Leroux et al, 1995;Desmeules et al, 2003;Banic et al, 2004;Coffin et al, 2004). However, it is still unclear whether reflex size is similarly affected by central sensitization (Andersen et al, 1995;Andersen et al, 1996;Arendt-Nielsen et al, 1994;Manresa et al, 2010). Moreover, noxious conditioning stimuli capable of inducing central sensitization may also trigger endogenous pain modulatory systems.…”
Section: Introductionmentioning
confidence: 99%
“…The assessments consisted of neurogenic inflammation imaging using laser speckle blood-flow imagery for measuring superficial blood flow (SBF) and infrared thermography for measuring skin temperature (ST), assessments of pinprick and light-stroking perception intensities surrounding the conditioned site (heterotopic), perceived intensity to homotopic single electrical stimulation (SES) and heat pain threshold (HPT) at the conditioned site. To evaluate perceived stimulation intensity, a VAS was used that was anchored from 0 (no sensation) to 100 (the most intense pain imaginable) where 30 indicated the pain threshold [ 28 , 30 32 ]. The same researcher performed all experiments to rule out the inter-rater variation.…”
Section: Methodsmentioning
confidence: 99%
“…The stimulations were applied with an epicutaneous pin electrode (EPE) consisting of a circular array (diameter: 10 mm) of fifteen cathodal electrodes each with diameter of 0.2 mm, protruding 1 mm from the base, and a large circular stainless steel plate served as an anode with an inner diameter of 20 mm and an outer diameter of 40 mm placed concentrically around the cathodes (Fig. 1A) (Biurrun Manresa et al, 2010). This electrode has been verified to induce a sensation of pain at a lower stimulation intensity compared with conventional cutaneous nerve stimulation because the diameter of the cathodes is smaller so a high current density is achieved in the epidermal layers where the nociceptive Aδ-and C fibers terminate (Kaube et al, 2000;Katsarava et al, 2006;Mouraux et al, 2010;Mørch et al, 2011).…”
Section: Conditioning Electrical Stimulation (Ces)mentioning
confidence: 99%